Chronic exercise alters EEG power spectra in an animal model of depression - Sarbadhikari S.N.; Dey S.; Ray A.K. (My University, 2025)
The EEG from frontal cortex, EMG and EEG were recorded from rats exposed to only exercise (Treadmill), only stress, exercise + stress and neither (control). In comparison with the control group, the percent of Delta activity in the awake was significantly increased in the depressed group and significantly decreased in the exercised groups, while for Beta-2, the reverse occurred; Theta increased and Beta-2 decreased in the NREM sleep state of the depressed group and the opposite happened for the exercised groups; Delta and Alpha-2 activity significantly increased in the depressed group, and they were significantly decreased in the exercised groups whereas the Beta-2 activity showed contrary changes in the REM sleep state. These findings indicate that exercise has the opposite effect from what stress has on qEEG and concomitant physical exercise reduces the effects of stress. Behavioral tests were done by Open Field (OF) and High Plus Maze (HPM). Slow EEG activity (Delta, Theta, Alpha) was significantly positively correlated with immobilization in the OF and defecation in both OF and HPM and negatively with the food intake, transfer latency in HPM; rearing, grooming and total ambulation in OF. Whereas, fast activity (Beta-2) was significantly negatively correlated with immobilization in OF and defecation in OF and HPM, while positively with ambulation in the central squares of OF and time spent at the central cross and number of times arms crossed in the HPM.